Colostomy in Anorectal Malformation and Hirschsprung’s Disease in Infants and Children - Zamil, Ali Laibi; Radhi, Osamah Abdul-Kadim; Hasan, Helen Samer (European Scientific Journal, ESJ, 2018)
Background: There are numerous and frequent common complications following construction of large bowel stomas, which may lead to significant morbidity and mortality. The overall morbidity from colostomy has been reported to be as high as 42-75%. Aims of the study: •To study the complications of colostomy (immediate, early & late) taking into consideration the site and types of the colostomy. •To determine the types and sites of colostomy in anorectal malformation and Hirschsprung’s disease. •To study some associated risk factors in colostomy with anorectal malformation and Hirschsprung’s Disease. •To estimate the rate of death for performed colostomies in anorectal malformation and Hirschsprung’s disease. Patients and methods: A cross-sectional prospective study included a total number of (160) temporary colostomies were performed for neonates, infants and children in the pediatric surgical department of Children Welfare Teaching Hospital in Baghdad over a period of three years from January 2008 to January 2011. A standardized data sheets were prepared for collecting the information including age, sex, associated congenital anomalies and colostomy data (type, site, indication, and complication). Results: Most of the colostomies were done in the neonatal period (69.4%) and mainly for imperforate anus (46.9%) while colostomies that were performed in infancy (26.2%) were done mainly for Hirschsprung’s disease (18.1%). The most common type of stoma was right loop transverse colostomy for Hirschsprung’s disease (31.2%) and pelvic loop for imperforate anus (42.5%). 107 different complications developed in 71 patients as a result of colostomy formation and the most common complications were stomal prolapse, skin excoriation, wound sepsis, stomal stenosis, retraction, and bleeding. The mortality rate was 7.5% (12 patients); 4 patients had Hirschsprung’s disease and 8 patients had an imperforate anus.Conclusion: Hirschsprung’s disease and imperforate anus were the most common indications of stoma formation in pediatric age group. The right transverse loop and pelvic loop colostomy were the commonest stoma that was performed with a high rate of complications.